Proceedings of the URECA@NTU 2021-2022 - Students of URECA Programme (2023)
The "Proceedings of the URECA@NTU 2021-2022" represents a curated collection of exceptional research papers produced during the 2021-22 academic year. These papers encompass URECA, Interdisciplinary-URECA, and Final Year Project-URECA initiatives, all crafted under the dedicated guidance of respective URECA supervising professors.